Decoding SFRP2 progenitors in sustaining tooth growth at single-cell resolution - Tianyuan Zhao; Qing Zhong; Zewen Sun; Xiaoyi Yu; Tianmeng Sun; Zhengwen An (Stem Cell Research & Therapy)
Abstract Background Single-cell transcriptomics has revolutionized tooth biology by uncovering previously unexplored areas. The mouse is a widely used model for studying human tissues and diseases, including dental pulp tissues. While human and mouse molars share many similarities, mouse incisors differ significantly from human teeth due to their continuous growth throughout their lifespan. The application of findings from mouse teeth to human disease remains insufficiently explored. Methods Leveraging multiple single-cell datasets, we constructed a comprehensive dental pulp cell landscape to delineate tissue similarities and species-specific differences between humans and mice. Results We identified a distinct cell population, Sfrp2hi fibroblast progenitors, found exclusively in mouse incisors and the developing tooth root of human molars. These cells play a crucial role in sustaining continuous tissue growth. Mechanistically, we found that the transcription factor Twist1, regulated via MAPK phosphorylation, binds to the Sfrp2 promoter and modulates Wnt signaling activation to maintain stem cell identity. Conclusions Our study reveals a previously unrecognized subset of dental mesenchymal stem cells critical for tooth growth. This distinct subset, evolutionarily conserved between humans and mice, provides valuable insights into translational approaches for dental tissue regeneration and repair. Graphical abstract